Tecnologias da informação e comunicação, direito à informação pública e debate acerca da corrupção no estado democrático de direito - Goulart, Gil Monteiro (2019)
The increasing investments in the use of Information and Communication Technologies (ICT) by the Brazilian public power have been done both to improve the efficiency of services provided and to help access to information and the exercise of social control. However, there have been recurrent the news of scandals regarding misuse of public resources, which shows that the problem of corruption is significant in Brazil and does not retreating before initiatives to publish public accounts already undertaken in the country. In this sense, the present study aims to analyze the institutional initiatives mediated by ICT adopted in the country to promote transparency in public accounts and fight against corruption, verifying their permeability to popular participation and their convergence with the citizens' wishes expressed in the E-democracy Portal. The need debate on corruption mechanisms has been a recurrent issue in the media, raising interest from both experts and politicians, as well as citizens. Considering the importance of the subject and the investments made in the country with a view to use of ICT in the public sector, it is questioned: within the institutional initiatives to debate on corruption by using ICT, is it possible to affirm that E-democracy Portal of the Chamber of Deputies is permeable to participation of citizens in the delineation of laws and policies concerning the debate on corruption? Based on this question, the present study uses the method of deductive approach, anchoring the research in the question regarding the increasing use of ICT for the performance of collaborative process of construction of legislative texts. In addition, the monographic procedure method and non-participative direct observation is used, performing the verification of manifestations expressed in E-Democracy portal of the Chamber of Deputies. The analysis of this portal demonstrates that it has potential to enable citizens' participation in the process of joint drafting of the legal provisions, which are combative measures to corruption. The current state of the issue allows concluding that popular participation through the digital platform that stores the agenda of draft bills advances in shy way, because the spaces lack a better dynamic between the diffusion of the theme and the promotion of debates among the citizens themselves.